2015
DOI: 10.1155/2015/385682
|View full text |Cite
|
Sign up to set email alerts
|

Antifibrotic Activity of Acylated and Unacylated Ghrelin

Abstract: Fibrosis can affect almost all tissues and organs, it often represents the terminal stage of chronic diseases, and it is regarded as a major health issue for which efficient therapies are needed. Tissue injury, by inducing necrosis/apoptosis, triggers inflammatory response that, in turn, promotes fibroblast activation and pathological deposition of extracellular matrix. Acylated and unacylated ghrelin are the main products of the ghrelin gene. The acylated form, through its receptor GHSR-1a, stimulates appetit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 95 publications
1
10
1
Order By: Relevance
“…This phenomenon was unexpected previously for ghrelin that can stimulate GH secretion and promote cell proliferation . However, ghrelin has been also reported to possess antifibrotic property . Otherwise, in another in vitro experiment, we found that ghrelin decreased the proliferative activity of HaCaT epidemic cells instead of improving it (data not shown); however, ghrelin increased the cell viability of irradiated HaCaT epidemic cells in a dose‐dependent manner (data not shown).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…This phenomenon was unexpected previously for ghrelin that can stimulate GH secretion and promote cell proliferation . However, ghrelin has been also reported to possess antifibrotic property . Otherwise, in another in vitro experiment, we found that ghrelin decreased the proliferative activity of HaCaT epidemic cells instead of improving it (data not shown); however, ghrelin increased the cell viability of irradiated HaCaT epidemic cells in a dose‐dependent manner (data not shown).…”
Section: Discussionsupporting
confidence: 73%
“…In chronic liver injury and fibrogenesis, ghrelin was reported to mitigate liver injury and inhibit fibrogenesis by NO release . In other studies, ghrelin was also proved to be an antifibrotic reagent partly by reducing collagen production through the inhibition of TGF‐β signalling pathway . However, our study indicated that ghrelin promoted NO and TGF‐β synthesis and collagen formation in the early stage of wound healing in CRWI mice.…”
Section: Discussioncontrasting
confidence: 62%
“…; Angelino et al. ). Interventions targeting excessive fibrosis as a result of MI are of major therapeutic importance in the treatment of HF (Samuel et al.…”
Section: Discussionmentioning
confidence: 98%
“…The GHS-R appears to mediate the action of HEX (Mao et al 2013(Mao et al , 2014a. The antifibrotic effects of GHS have been investigated with promising results in various models of cardiac injury such as doxorubicin cardiotoxicity isoproterenol administration, myocardial infarction, and spontaneous or diabetes-associated hypertension (Angelino et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…What is more, ghrelin modifies the function of fibroblasts and reduces their production of collagen. Indirectly, by limiting the penetration of inflammatory cells into the damaged tissue and reducing the release of cytokines responsible for fibroblast activation and directly, by blocking the TGF‐β signaling pathway . Another mechanism responsible for the influence of ghrelin on the healing process, as it was demonstrated in a study by Kwan et al, is the reduction of microvascular leaks during inflammation through the GHS‐R1a‐mediated NF‐κB pathway.…”
Section: Discussionmentioning
confidence: 99%